The History of Terrorism in Indonesia and Efforts to Prevent Terrorism in Indonesia - Maulida, Yunita Prananda (Universitas Negeri Semarang, 2017)
Terrorism is an extraordinary crime that is a challenge for the Indonesian people to abolish it. Terrorism usually starts from radical views or understandings by a particular person or group to threaten the government and make anxious Indonesian people. Because terrorism is very detrimental to the nation and state of Indonesia psychologically and materially, it is appropriate for the Indonesian people to fight the spread of understanding that can trigger acts of terrorism. One way is to strengthen the values of Pancasila to all the people of Indonesia. The purpose of this paper is for the Indonesian people to know the bitter history of acts of terrorism that have occurred in Indonesia almost every year. And also so that the Indonesian people can prevent the spread of radical thinking and always uphold the four pillars of Indonesian nationality. The thought that must be owned by the successor of the Indonesian nation is tolerance, this is due to the condition that Indonesia is a country that has many differences in many ways.